\documentclass[reqno]{amsart} \usepackage{hyperref} \AtBeginDocument{{\noindent\small \emph{ Electronic Journal of Differential Equations}, Vol. 2008(2008), No. 25, pp. 1--6.\newline ISSN: 1072-6691. URL: http://ejde.math.txstate.edu or http://ejde.math.unt.edu \newline ftp ejde.math.txstate.edu (login: ftp)} \thanks{\copyright 2008 Texas State University - San Marcos.} \vspace{9mm}} \begin{document} \title[\hfilneg EJDE-2008/25\hfil Existence of solutions] {Existence of solutions for some third-order boundary-value problems} \author[Z. Bai\hfil EJDE-2008/25\hfilneg] {Zhanbing Bai} \address{Zhanbing Bai \newline Institute of Mathematics, Shandong University of Science and Technology\\ Qingdao 266510, China} \email{zhanbingbai@163.com} \thanks{Submitted September 21, 2007. Published February 22, 2008.} \thanks{Supported by grant 10626033 from the Tianyuan Youth Grant Office of China} \subjclass[2000]{34B15} \keywords{Third-order boundary-value problem; lower and upper solutions; \hfill\break\indent fixed-point theorem} \begin{abstract} In this paper concerns the third-order boundary-value problem \begin{gather*} u'''(t)+ f(t, u(t),u'(t), u''(t))=0, \quad 0 < t < 1, \\ r_1 u(0) - r_2 u' (0)= r_3 u(1) + r_4 u'(1)= u''(0)=0. \end{gather*} By placing certain restrictions on the nonlinear term $f$, we prove the existence of at least one solution to the boundary-value problem with the use of lower and upper solution method and of Schauder fixed-point theorem. The construction of lower or upper solutions is also presented. \end{abstract} \maketitle \numberwithin{equation}{section} \newtheorem{theorem}{Theorem}[section] \newtheorem{lemma}[theorem]{Lemma} \newtheorem{definition}[theorem]{Definition} \newtheorem{example}[theorem]{Example} \newtheorem{remark}[theorem]{Remark} \section{Introduction} Recently, third-order boundary-value problems have been considered in many papers. Some problems of regulation and control of some actions by a control level or by a signal reduce to solving the third-order equations. Other applications of third-order differential equations are encountered in the control of a flying apparatus in cosmic space, the deflection of sandwich beam, and the study of draining and coating flows. For details, see the references in this article and the references therein. As it is pointed out by Anderson {\it et al.} \cite{a1}, a large part of the literature on solution to higher-order boundary-value problems seems to be traced to Krasnosel'skii's work on nonlinear operator equations as well as other fixed-point theorem such as Leggett-Williams' fixed-point theorem. The method of upper and lower solution is extensively developed for lower order equations with linear and nonlinear boundary conditions. But there are only a few applications to higher-order ordinary differential equations. For applications to higher-order ODEs, we refer the reader to Ehme \cite{e1}, Klaasen \cite{k1} and the references therein. Specially, in Cabada \cite{c1} and Yao \cite{y1}, the lower and upper solution method is employed to acquire existence results about some third-order boundary-value problems with some monotonic or quasi-monotonic nonlinear term $f$ which is no dependence on any lower-order derivatives. On the other hand, to my best knowledge, there are few papers referred to lower and upper solutions of third-order equation consider the relationship between the property of nonlinear term and the construction of lower and upper solutions. The purpose of this paper is to study the existence of solution for two class nonlinear third-order boundary-value problems \begin{gather} u'''(t)+ f(t,u(t),u''(t))=0, \quad 0 \leq t \leq 1, \label{e1}\\ r_1 u(0) - r_2 u' (0)=r_3 u(1) + r_4 u' (1)= u''(0)=0, \label{e2} \end{gather} and \begin{gather} u'''(t)+ f(t,u(t),u'(t),u''(t))=0, \quad 0 \leq t \leq 1, \label{e3} \\ u(0) = u'(1)= u''(0)=0.\label{e4} \end{gather} The method used here is not based on the Krasnosel'skii's fixed-point theorem or monotonic operator theory; rather, it is based on Schauder fixed-point theorem, the appropriate integral transvestites and lower and upper solution method. The construction of lower or upper solution is also presented. \section{Preliminaries} In this section, we consider \eqref{e1}--\eqref{e2}, under the assumption that $f:[0, 1] \times R^2 \to R$ is continuous, $r_1, r_2, r_3, r_4 \geq 0$ and $\rho := r_2r_3 + r_1r_3 + r_1r_4 >0$. We give some lemmas which indicate some restrictions on the nonlinear term and let us construct lower or upper solutions. \begin{definition} \label{def2.1} \rm We call $\alpha$, $\beta \in C^2[0, 1]\bigcap C^3(0, 1)$ lower and upper solutions of Problem \eqref{e1}--\eqref{e2}, respectively, if \begin{gather*} \alpha'''(t)+ f(t,\alpha(t),\alpha''(t)) \geq 0,\quad 0 < t < 1, \\ r_1\alpha(0) - r_2\alpha' (0)= r_3\alpha(1) + r_4\alpha'(1)=0, \quad \alpha''(0) \geq 0; \end{gather*} \begin{gather*} \beta'''(t)+ f(t,\beta(t),\beta''(t))\leq 0, \quad 0 < t < 1,\\ r_1\beta(0) - r_2\beta' (0)= r_3\beta(1) + r_4\beta'(1)=0, \quad \beta''(0) \leq 0. \end{gather*} \end{definition} Denote by $G(t, s)$ the Green's function of $$\begin{gathered} -u''(t) = 0, \quad 0 < t < 1, \\ r_1u(0)-r_2u' (0)= r_3u(1) + r_4u'(1)=0, \end{gathered} \label{e5}$$ then $$G(t, s) = \begin{cases} \frac{1}{\rho}x(t)y(s), & 0 \leq s < t \leq 1, \\ \frac{1}{\rho}x(s)y(t), & 0 \leq t < s \leq 1, \end{cases} \label{e6}$$ where $x(t):= r_3+r_4-r_3t$, $y(t) := r_2+r_1t$, for $t \in [0, 1]$, $\rho = r_2r_3 + r_1r_3 + r_1r_4$. Clearly, $G(t, s) \geq 0$ for $0 \leq t, s \leq 1$. The following Lemma comes from Lian \cite{l1} with small modification. \begin{lemma}[\cite{l1}] \label{lem2.1} For $G(t, s)$ defined by \eqref{e6}, the following holds: \begin{itemize} \item[(R1)] $\frac{G(t, s)}{G(s, s)} \leq 1$ for $t,s \in (0, 1)$, \item[(R2)] $\frac{G(t, s)}{G(s, s)} \geq C=:\min \{ \frac{r_4}{r_3+r_4}, \frac{r_2}{r_1+r_2}\} \geq 0$, for $t, s \in (0,1)$. \end{itemize} \end{lemma} Let $\eta = \int_0^1 G(s, s)s\,ds >0$. Then we have the following results. \begin{lemma} \label{lem2.2} If there exists a constant $M \geq 0$ such that $$f(t,s,r) \leq M, \quad\text{for } 0\leq t \leq 1,\; \eta M C\leq s \leq \eta M, \; - M \leq r \leq 0,$$ then Problem \eqref{e1}-\eqref{e2} has an upper solution. \end{lemma} \begin{proof} Setting $v(t) = -u''(t)$, Problem \eqref{e1}--\eqref{e2} is equivalent to \begin{gather} v'(t) = f(t, (Av)(t), -v(t)), \quad 0 < t < 1,\label{e7} \\ v(0)= 0, \quad \label{e8} \end{gather} where $(Av)(t) = \int_0^1G(t,s)v(s)ds$ and $G(t, s)$ is defined by \eqref{e6}. It is clear that the restriction on $f$ guarantee that $\psi (t) = Mt$ satisfies \begin{gather*} \psi'(t) - f(t, (A\psi)(t), -\psi(t))\geq 0, \quad 00$such that$\beta(t) = \int_0^1G(t, s)Ms\,ds$is an upper solution of \eqref{e1}--\eqref{e2}. If the nonlinear term$ f $satisfies $$\underline f_\infty = \liminf_{u \to - \infty} \min_{0 \leq t \leq 1} \frac{f(t, \eta u, -u)}{u} \leq 1,$$ then there exists$N<0$such that$\alpha(t) = \int_0^1G(t, s)Ns\,ds\$ is a lower solution of \eqref{e1}--\eqref{e2}. \end{remark} \begin{example} \label{exa1} \rm Consider the problem \begin{gather} u'''(t) + \frac{1}{3} [t + \ln (1+u(t))-u''(t)]=0, \quad 0